2020
DOI: 10.1002/jimd.12236
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variability in newborn metabolic screening markers associated with false‐positive outcomes

Abstract: Newborn screening (NBS) programmes utilise information on a variety of clinical variables such as gestational age, sex, and birth weight to reduce false‐positive screens for inborn metabolic disorders. Here we study the influence of ethnicity on metabolic marker levels in a diverse newborn population. NBS data from screen‐negative singleton babies (n = 100 000) were analysed, which included blood metabolic markers measured by tandem mass spectrometry and ethnicity status reported by the parents. Metabolic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…At AaBC under 72 h, the four selected metabolites displayed similar patterns in relation to differences in GA, sex and ethnicity, while patterns changed at AaBC after 96 h. A potential cause for these changes could be limitations in sample size, which decreased with increasing AaBC (97–120 h: n = 1657; 121–144 h: n = 627; 145–168 h: n = 326) leading to increased variance of the estimated mean. Other reasons for the metabolic pattern changes related to later AaBC may be the postnatal advance and increasing environmental changes, or differences related to race/ethnicity status ( 17 , 25 ). We found that White infants had a tendency for later blood collection (26.0% between 24–48 h, 32.6% between 49–168 h, P < 0.001), which could lead to differences in metabolic patterns in later AaBC groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At AaBC under 72 h, the four selected metabolites displayed similar patterns in relation to differences in GA, sex and ethnicity, while patterns changed at AaBC after 96 h. A potential cause for these changes could be limitations in sample size, which decreased with increasing AaBC (97–120 h: n = 1657; 121–144 h: n = 627; 145–168 h: n = 326) leading to increased variance of the estimated mean. Other reasons for the metabolic pattern changes related to later AaBC may be the postnatal advance and increasing environmental changes, or differences related to race/ethnicity status ( 17 , 25 ). We found that White infants had a tendency for later blood collection (26.0% between 24–48 h, 32.6% between 49–168 h, P < 0.001), which could lead to differences in metabolic patterns in later AaBC groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examining the association between AaBC and MS/MS-based screening have focused on a single or a few metabolic analytes or groups of metabolic disorders ( 4 9 ). In addition to AaBC, metabolic changes have also been associated with other confounding clinical variables such as gestational age (GA), birth weight (BW), sex, season of birth and race/ethnicity status reported by the parents ( 10 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…and/or C3/C2 ratio; Peng et al, 2019) and increased levels of C3 levels in Hispanic newborns generally (Peng, Tang, Gandotra, et al, 2020). More studies are required to confirm this overrepresentation Hispanic newborns with elevated C3.…”
Section: Discussionmentioning
confidence: 96%
“…In our study all of pseu- (Ross, 2008), the importance of screens including secondary mechanisms to reduce false positive rates is essential to build trust. Furthermore, the field is accumulating evidence of many types of markers and the ethnic risk for false positive rates (described and reviewed in Peng et al, 2020). Thus, this work is another piece of the complex puzzle to create a newborn screen that ensures the highest sensitivity and specificity possible for each newborn.…”
Section: Pseudodeficiency Allelesmentioning
confidence: 99%
“…Identifying true positives in a population can be challenging due to a broad range of biochemical cut-offs, barriers to follow-up testing, limited access to genetic sequencing, and lack of available genetic providers with knowledge on interpretation of results. Differences in metabolic screening markers may vary based on the infants' ethnic background resulting in false-positive reporting (Peng et al, 2020;Wasserstein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%